2019
DOI: 10.1155/2019/5395676
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Changes over the CORDEX-MENA Domain in the 21st Century Using CMIP5 Data Downscaled with RegCM4: A Focus on the Arabian Peninsula

Abstract: This paper examined the temperature changes from the COordinated Regional climate Downscaling Experiment (CORDEX) over the Middle East and North Africa (MENA) domain called CORDEX-MENA. The focus is on the Arabian Peninsula in the 21st century, using data from three Coupled Model Intercomparison Project Phase 5 (CMIP5) models downscaled by RegCM4, a regional climate model. The analysis includes surface observations along with RegCM4 simulations and changes in threshold based on extreme temperature at the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 46 publications
3
21
0
Order By: Relevance
“…This large rate of increase in surface temperature over the Peninsula causes many temperature extremes in the region and indicates the need for a disaster management program [5]. In a recent study Almazroui et al [6] presented evidence that during the 21st century, temperature over the Peninsula will warm at a faster rate than over the larger COordinated Regional climate Downscaling Experiment (CORDEX) Middle-East and North Africa (MENA) domain. In addition to this rise in temperature, changes in precipitation were also observed over the Peninsula.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This large rate of increase in surface temperature over the Peninsula causes many temperature extremes in the region and indicates the need for a disaster management program [5]. In a recent study Almazroui et al [6] presented evidence that during the 21st century, temperature over the Peninsula will warm at a faster rate than over the larger COordinated Regional climate Downscaling Experiment (CORDEX) Middle-East and North Africa (MENA) domain. In addition to this rise in temperature, changes in precipitation were also observed over the Peninsula.…”
Section: Introductionmentioning
confidence: 99%
“…Some information on climate extremes over the Arabian Peninsula is also available from analysis using IPCC AR4 (CMIP3) and AR5 (CMIP5) multi-models data [18]. However, to the best of our knowledge, details on the analysis of extremes using CMIP5 multi-models downscaled by regional climate model and compared with the observations are not available for the region except for the work of Almazroui [6] who showed that threshold based warm days (Tmax ≥ 50 • C) will increase and cold nights (Tmin ≤ 5 • C) will decrease faster over the Arabian Peninsula than over the wider region. Nevertheless, no climate model simulation is free from uncertainty and that in particular, the simulation of precipitation and temperature on a daily scale is a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…We choose ERA-Interim as our driver field because ERA-Interim was, at the time of simulations, one of the best available reanalysis products (e.g., [22,38]). Furthermore, both ERA-Interim and its predecessor ERA-40 have been extensively used in similar downscaling studies focusing on analysis of regional climate change across different regions around the world and as proxy for observations (e.g., [20,26,[37][38][39][40]); most importantly, they have been used in this context over the AP (e.g., [6,11,41]).…”
Section: Numerical Experiments and Supporting Datamentioning
confidence: 99%
“…The Kingdom of Saudi Arabia (KSA) has a dry, hot climate with infrequent rainfall (e.g., [1]). Several studies show increasing trends in temperatures in station observations across KSA (e.g., [2][3][4][5]) as well as in gridded observational products (e.g., [6]). For example, Almazroui et al (2014) investigated the trends of extreme temperatures in Saudi Arabia using observations from 27 ground-based stations for 30 years (1981-2010) and found that temperature extremes were higher in magnitude and more frequent for both cold and warm extremes during the most recent decade (1996-2010) of their analysis [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation